Czy możemy mieć pojęcie czasu? - JUSIAK, Janusz (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
In the article, the reasons which render impossible a virtually universal concept of time are analyzed. The most important among them is that any attempt at the conceptualization of time involves a direct or indirect recourse to metaphor, which inevitably enters the descriptions of the nature of time expressed in language. Residual forms of metaphor can be traced even in the conceptions of time developed in the natural sciences. The belief in the allegedly mysterious nature of time is also subject to criticism. Translated by Dorota Chabrajska